The relationship of knowledge management and innovation towards the organization at Top Glove Sdn.Bhd / Norhaidah Ahmad - Ahmad, Norhaidah (2014)
The purpose of this research is describes about the relationship of knowledge management practices and the innovation in the organization performance. This paper was correlational and descriptive statistic research which is showed the knowledge management in Top Glove Sdn. Bhd. The knowledge management practice is very important to the innovation for the organization. Nevertheless, this paper in only tell us about intangible knowledge management and tangible knowledge management. The data was gathered by using the questionnaires method that had answered by 150 middle staffs of both companies. This research is using the sampling cluster which is can save the time during doing this research. The study finds that the level of knowledge management practices and the organizational performance in private staff for the company are moderate. Then, the hypothesis was accepted where there have a significant relationship between knowledge management practices and innovation in private sectors. Hence, based on finding, knowledge management practices was totally influenced organizational performance. Other than that, these research in tell us about the knowledge management, which is includes in three separated terms. There is knowledge acquisition, knowledge dissemination and responsiveness to knowledge. Moreover, these research also tell about innovation can get the effect of the staff knowledge in that company.